PENDAMPINGAN ANGGOTA UKS DALAM MELAKUKAN AKUPRESUR UNTUK MENINGKATKAN SISTEM KONSENTRASI BELAJAR DAN PEMBUATAN DESAIN FORMULIR STATUS KESEHATAN DI SMA - Nurul Faidah; I Made Sudarma Adiputra; Ni Luh Gede Puspita Yanti; Ni Putu Wiwik Oktaviani; Ni Kadek Muliawati (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Learning requires students' readiness to take lessons in class when studying individually or in groups. Learning concentration is a form of student readiness in participating in the learning process. To increase the concentration of learning needs to be done acupressure therapy. Acupressure is useful for smoothing blocked blood flow, by pressing certain points it is believed to improve concentration, focus and memory. Apart from implementing acupressure to document the health status of students, socialization of student health records was carried out in schools. The purpose of the community service is to socialize acupressure therapy to increase learning concentration and socialize the Health status form to school-age children. The method is carried out using online methods or online materials in the form of simulations in conducting acupressure therapy and socialization related to student health documentation in target schools in the service of high school students. The results of the implementation of student community service were attended by 20 students and students understood acupressure techniques to increase learning concentration and documentation of health status in schools.